2023
DOI: 10.3390/vaccines11030698
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of High-Grade Cervical Dysplasia with Positive Margins and HPV Persistence after Cervical Conization

Abstract: The objective of this work is to assess the 5-year outcomes of patients undergoing conization for high-grade cervical lesions that simultaneously present as risk factors in the persistence of HPV infection and the positivity of surgical resection margins. This is a retrospective study evaluating patients undergoing conization for high-grade cervical lesions. All patients included had both positive surgical margins and experienced HPV persistence at 6 months. Associations were evaluated with Cox proportional ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Accumulating evidence has provided strong and consistent data that HPV persistence is the main factor influencing the risk of developing HPV-related disease, including cervical dysplasia and cervical cancer (Casarin et al ., 2020; Falcaro et al ., 2021; Mix et al ., 2022; Di Donato et al ., 2023; Giannini et al ., 2023). Duration of HPV persistence, viral load, deregulation of HPV gene expression, and host epigenetic mechanisms (including methylation of imprinted gene control) are the main factor influencing the process of tissue transformation (Smith et al ., 2022; Cicconi et al ., 2022; Demarco et al ., 2022; Mix et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has provided strong and consistent data that HPV persistence is the main factor influencing the risk of developing HPV-related disease, including cervical dysplasia and cervical cancer (Casarin et al ., 2020; Falcaro et al ., 2021; Mix et al ., 2022; Di Donato et al ., 2023; Giannini et al ., 2023). Duration of HPV persistence, viral load, deregulation of HPV gene expression, and host epigenetic mechanisms (including methylation of imprinted gene control) are the main factor influencing the process of tissue transformation (Smith et al ., 2022; Cicconi et al ., 2022; Demarco et al ., 2022; Mix et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…This difference might be due to the lack of health education programs regarding cervical cancer vaccination in the urban slum, which is believed to be the problem of most developing countries [ 41 ]. Certain strategies have been suggested in literature including the use of nomograms in the sensitization of women [ 42 ] and also showing the women results of outcomes from women with cervical cancer as a way of making them realise why preventive behaviour is important [ 43 ]. The level of awareness and knowledge of cervical cancer, its aetiology, screening as well as HPV vaccination in women can greatly influence their participation in screening and vaccination programs [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…22 Among these, types 16,18,31,33,35,39,45,51,52,56, and 58 are classified as high-risk types, while another six genotypes (26, 53, 66, 68, 73, and 82) are considered as probably high-risk types. HPV 6,11,40,42,43,44,54,61,70,72, and 81 are considered low-risk types associated with genital warts and low-grade CIN. 21 While genotypes 6 and 11 are associated with anogenital warts.…”
Section: Hpv and Related Malignanciesmentioning
confidence: 99%
“…A recent study by Giannini et al (2023) 43 examined the effects of conization in women with high-grade cervical dysplasia, positive margins and HPV continuities. Findings revealed that although these have a higher risk of recurrence, they still have a similar overall survival rate compared to women without these risk factors.…”
Section: Hpv Prevention and Global Burdenmentioning
confidence: 99%
See 1 more Smart Citation